2011
DOI: 10.1016/j.optlaseng.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fracture toughness of ZrO2 and Si3N4 engineering ceramics following CO2 and fibre laser surface treatment

Abstract: The fracture toughness property (K 1c ) of Si 3 N 4 and ZrO 2 engineering ceramics was investigated by means of CO 2 and a fibre laser surface treatment. Near surface modifications in the hardness was investigated by employing the Vickers indentation method. Crack lengths and geometry were then measured by using the optical. A coordinate measuring machine was used to investigate the diamond indentations and to measure the lengths of the cracks. Thereafter, computational and analytical methods were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Typically, laser beam absorption also depends on the particular wavelength applied at the material surface. Particularly for ceramics, laser in the range of 1µm wavelength and under, tends to produce sufficient absorption [14][15][16][17] . …”
Section: Laser Peening Fundamentalsmentioning
confidence: 99%
“…Typically, laser beam absorption also depends on the particular wavelength applied at the material surface. Particularly for ceramics, laser in the range of 1µm wavelength and under, tends to produce sufficient absorption [14][15][16][17] . …”
Section: Laser Peening Fundamentalsmentioning
confidence: 99%
“…Their work show that tailoring LSP parameters can increase the surface hardness of alumina by up to 100% and the fracture toughness by 42%. Shukla and Lawrence applied the CO 2 and the fiber laser surface treatment to increase the fracture toughness of ZrO 2 and Si 3 N 4 ceramics . It was observed that the fracture toughness modification of these ceramics was influenced by different laser wavelengths and its absorption coefficient, the beam delivery system, and the brightness of the lasers .…”
Section: Introductionmentioning
confidence: 99%
“…Shukla and Lawrence applied the CO 2 and the fiber laser surface treatment to increase the fracture toughness of ZrO 2 and Si 3 N 4 ceramics . It was observed that the fracture toughness modification of these ceramics was influenced by different laser wavelengths and its absorption coefficient, the beam delivery system, and the brightness of the lasers . These early studies attributed the improved mechanical properties to the compressive residual stress induced by LSP, but did not elucidate the microscale mechanistic mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…The beam travelled the length of 7 mm across the width of the as-received (laser unaffected) HAZ and the laserengineered surfaces areas. Mechanical effects such as change in hardness were investigated by using the Vickers indentation (Vickers (HVTM); Armstrong Engineering, Ltd.), which was followed by a calculation of the fracture toughness parameter (K 1c ) using empirical equations from the literature [48][49][50][51]. The temperature measurement was conducted using an infrared thermometer device (Cyclops 100 B; Land instruments international Ltd.) on the surface and also by using a precision fine wire (0.20 diameter  152 mm in length), R-type thermocouple (P13R, Omega Instruments Ltd.).…”
Section: Characterization Techniquesmentioning
confidence: 99%